Endophytes and Rhizosphere Fungi from Galam (Melaleuca cajuputi Powell.) which has the Potential to Produce Indole Acetic Acid (IAA) - Witiyasti Imaningsih; Nadiya Dwi Rahayu; Safinah Surya Hakim (Universitas Gadjah Mada, 2021)
Some types of fungi are known to have the ability to produce Indole Acetic Acid (IAA). Fungi can be isolated from the rhizosphere and tissues of various plants, including from the rhizosphere and the root